Multilevel Fuzzy Mamdani Method for Assessing the Health of Sharia Cooperation - Andayani, Sri; Fauziah, Asyifa (Jurnal Sains Dasar, 2024)
This study aims to develop rules for assessing the health of the Sharia Savings and Loans Cooperation using the multilevel Mamdani Fuzzy Inference System. This assessment process is carried out in two level, the first is dividing the assessment criteria into three categories, namely Assessment A relating to capital, Assessment B relating to management, and Assessment C relating to the principles of Islamic cooperatives. Using MAPE as a measure of assessment accuracy, the findings reveal at the first level that assessment A's accuracy is 91.21%, assessment B's is 90.05%, and assessment C's is 91.96%. At the second level, the multilevel Mamdani Fuzzy Inference System uses the outputs from the three assessment groups as input to determine the overall health of the cooperation with an accuracy of 92.63%. It can be concluded that the health assessment of the Sharia Savings and Loans Cooperation using the multilevel Mamdani Fuzzy Inference method has good accuracy.